The assassin [large type] - Cussler, Clive; Scott, Justin (Cussler, Clive. Isaac Bell novels, 2015)
As Van Dorn private detective Isaac Bell strives to land a government contract to investigate John D. Rockefeller's Standard Oil monopoly, the case takes a deadly turn, and a sniper begins murdering opponents of Standard Oil. Who is the assassin and for whom did he kill? Bell tracks his phantom-like criminal adversary from the "oil fever" regions of Kansas and Texas to Washington, D.C., to the tycoons' enclave of New York, to Russia's war-torn Baku oil fields on the Caspian Sea, and back to America for a final, desperate confrontation. And this one will be the most explosive of all.